TINGKAT KETERCUKUPAN SARANA DAN PRASARANA BENGKEL TEKNIK BISNIS SEPEDA MOTOR DI SMK MUHAMMADIYAH BANGUNJIWO TAHUN AJARAN 2020/2021 - kurnia wardani husnul khotimah; subagyo subagyo (JURNAL VOKASI DEWANTARA (JVD), 2022)
The research aims to: to determine the adequacy of the facilities and infrastructure of the Motorcycle Engineering workshop at SMK Muhammadiyah Bangunjiwo according to the real conditions in the workshop. The type of research used is descriptive type. The data collection techniques used in this research are observation, interviews and documentation. The research instrument uses the Observation Instrument sheet. The data analysis technique used is descriptive statistics. The research subject used in this research is the Productive Teacher majoring in Engineering. Motorbikes and the research object used in this study were the Motorcycle Engineering workshop including the facilities and infrastructure in the Motorbike Engineering workshop at SMK Muhammadiyah Bangunjiwo. The results showed that the adequacy level of the motorbike business engineering workshop infrastructure, namely the practice space was categorized as insufficient. After reviewing the Permendiknas No. 40 of 2008, the adequacy level of practical facilities for the Motorcycle Business Engineering Workshop which includes the main equipment and supporting equipment is categorized as sufficient.